Pengaruh Firm Size, Capital Intensity dan Beban Pajak Tangguhan terhadap Tax Avoidance pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Tahun 2020 – 2022 - Melawati, Desi; Ahalik, Ahalik (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Taxation is one of the main sources of income for the state, however state revenues from the taxation sector have not met the government's expectations every year. This is caused by government policies that are less effective in encouraging tax compliance and a lack of taxpayer awareness about tax payment obligations for industries and companies. This research aims to determine the influence of company size, capital intensity, tax burden on tax avoidance in food and beverage companies registered on the IDX in 2020-2022 and the simultaneous influence of company size, capital intensity, and deferred tax burden on tax avoidance in food and beverage companies listed on the BEI in 2020-2022. The method used in this research is a quantitative research method. In this research, the data used comes from secondary data. The data source used is the audited financial reports of companies registered on the Indonesian Stock Exchange (BEI) for the 2020-2022 period. This data can be accessed via the official IDX website, namely www.idx.co.id. The researcher used the ippurposive sampling method to select the sample, with independent variables in the form of company size, capital intensity and deferred tax burden and the dependent variable, namely tax avoidance. The data analysis methods used are descriptive statistical analysis, classical assumption testing, regression analysis, hypothesis testing and identification test. The results of this research show that Firm size has a significant negative effect on tax avoidance, Capital intensity has a significant negative effect on tax avoidance, Deferred tax burden has a significant positive effect on tax avoidance, and Firm size, capital intensity and deferred tax burden simultaneously have an effect on tax avoidance.